Legal Construction of Parameters Determining Default and Fraud in an Agreement - tajuddin noor (Warmadewa Press, 2025)
Legally made agreements are binding for the makers. However, in practice, contractors who do not perform their obligations are often prosecuted through criminal law based on Article 378 of the Criminal Code, giving rise to the perception of overlap between default and fraud. This pape analyzes the legal parameters to distinguish between default and fraud based on a normative juridical approach. This research uses secondary data consisting of primary, secondary, and tertiary legal materials. The results of the analysis show that default is born from contractual obligations based on agreements with indicators of good faith, while fraud is rooted in criminal acts based on malicious intent (mens rea) with indicators of a series of lies. This research recommends a strict separation between the civil and criminal domains to realize legal certainty